Analisis Exergoeconomic Pada Ruang Bakar Pembangkit Listrik Tenaga Gas Uap (PLTGU) Teluk Lembu 30 MW - Putri Wahyuni; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of the causes of the energy crisis in Indonesia is, because it is not efficient in energy use. Many alternatives have been done to make efficient use of energy. One way is to perform the analysis. Analysis meant here is the exergy analysis and analysis exergoeconomic. The concept of this analysis, not only of the quantity of energy but also the quality of energy (the second law of thermodynamics). Exergoeconomic analysis, is a technique that combines exergy analysis with the economic approach (cost). Exergoeconomic analysis is done by sampling Teluk Lembu combined cycle power plant . The analysis begins with the economic analysis. This analysis was conducted to determine the value of the total expenditures of the Teluk Lembu combined cycle power plant per year and electricity prices/kWh. The following four aspects of the calculated cost is the cost of investment, maintenance fixed operating costs, including employee salaries and benefits adjusted to the standard INKINDO 2014, fuel costs, maintenance and operating cost variable. Each value is, the cost of investment of IDR 196.03/kWh, the cost OM fix IDR 69.72/kWh, OM variable costs IDR 34.86/kWh, fuel costs IDR 1072.74/kWh. Loss value cost for combustion chamber is valued at IDR 8,338,282.46/h.Key Word : Exergy, Exergoeconomic, cost